Water Privatization and the Prospects for Trade Union Revitalization in the Public Sector: Case Studies from Bolivia and Peru - Spronk, Susan (Just Labour: A Canadian Journal of Work and Society, 2009)
Based on two case studies from Peru and Bolivia, this paper investigates why certain unions of water workers and not others have sought to form deep coalitions with community groups when confronted by privatization.